The Participatory-Action-Research. A way to research in the nursing practice - Abad Corpa, Eva; Delgado Hito, Pilar; Cabrero García, Julio (Investigación y Educación en Enfermería, 2010)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Within the qualitative research paradigm, the Participatory-Action- Research (PAR) integrates knowledge and action. It is not necessary to wait for knowledge to be produced to transfer it into practice. It is a method used for decades in disciplines such as education and sociology; however it is emerging in the health field. There are a variety of definitions, classifications and PAR models; this article aims to shed light upon this method of research, its history, philosophy and its use, given its potential and innovation in the field of health sciences.